2021
DOI: 10.33745/ijzi.2021.v07i02.008
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Free Radical Scavenging Activity of Cinnamomum tamala Leaf Extract

Abstract: Traditional plant-based medicines are still needed by the whole world for their primary healthcare benefits. The phytochemicals or plant extract could be used to treat different diseases and new formulation for the drug discovery in pharmaceuticals. Cinnamomum tamala is commonly called as Indian bay leaf or Tejpatta. The leaves and bark of Cinnamomum tamala are used to cure various diseases due to its various properties including astringent, stimulant and carminative. Hence, the objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Wells were bored, and then 2 mL of an extract made from Cinnamon impressinervium leaves was added to the medium. An hour was spent on inoculation to guarantee the strong diffusion of antimicrobial agents to the medium [10,18,19].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Wells were bored, and then 2 mL of an extract made from Cinnamon impressinervium leaves was added to the medium. An hour was spent on inoculation to guarantee the strong diffusion of antimicrobial agents to the medium [10,18,19].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Among the Cinnamomum species, the Cinnamomum tamala leaves exhibit various medicinal properties and used as a food flavor and spice (22). The leaves of Cinnamomum tamala shows various phytochemical properties with abundant presence of flavonoids, phenols, tannins, steroids and saponins (23). Phytochemical analysis of the leaf extract of Cinnamomum tamala revealed the presence of various bioactive compound which possess medicinal properties.…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…6 Plants have been used as complementary sources of medicines from centuries against various ailments due to their antioxidant, hypoglycaemic, hypolipidemic, hepatoprotective, neuroprotective, and nephroprotective activities, various therapeutics are prepared from medicinal plants for the treatment of diabetes and related complications. [7][8][9][10][11][12][13][14][15] Marvellous research has been conducted on pharmacotherapy, because traditional options of treatment could be better substitute of allopathic drugs, due various reasons such as ease of availability, costeffective and devoid side defects, 16,17 Pilot study revealed that Cinnamomum tamala and Taraxicum officinale leaves contains various bioactive components, these bioactive components might be helpful to combat worsen reproductive disorder. Considering the medicinal profile of these two leaf extract.…”
Section: Introductionmentioning
confidence: 99%